A functional variant in CHK1 contributes to increased risk of nasopharyngeal carcinoma in a Han Chinese population. Issue 5 (6th January 2020) - Guo, Zhen; Wang, Youhong; Zhao, Yu; Jin, Yi; An, Liang; Xu, Heng; Liu, Zhaoqian; Chen, Xiaoping; Zhou, Honghao; Wang, Hui; Zhang, Wei
Abstract: DNA damage checkpoints act as a supervisor by preventing the course of cell cycle upon DNA damage and keeping the steadiness of genome. Checkpoint kinase 1 (CHK1) cannot be ignore in the etiology of numerous human cancers including nasopharyngeal cancer (NPC). To discuss genetic polymorphisms of CHK1 rs492510 in the occurrence of NPC was our objective. Rs492510 polymorphism of CHK1 was genotyped in 684 patients with NPC and 823 cancer‐free controls. We utilize logistic regression models to appraise the correlation of rs492510 and susceptibility of NPC. Comparative expression level about CHK1 in nasopharyngeal carcinoma tissues were determined by real‐time polymerase chain reaction. And we made use of Dual‐Luciferase Reporter Assay to assess the transcriptional ability of CHK1 with different rs492510 allele. Adjusting multivariate logistic regression based on age, sex, body mass index, smoking, and drinking status showed that CHK1 rs492510 GA + GG genotype carriers presented prominent higher risk in NPC (odds ratio = 1.376, 95% confidence interval: 1.087‐1.742; P  = .008). As a consequence, we revealed that CHK1 relative expression levels in NPC tissues was higher than rhinitis tissues. Besides, the expressions of CHK1 in rs492510 GA genotype carriers were higher compared with people in AA genotype. The G allele of rs492510 generated remarkable higher transcription activity of CHK1 vs A allele by luciferase reporter assay. Our study considered that single nucleotide polymorphism rs492510 could increase transcription activity of CHK1 with the functionality, contributing to the susceptibility of NPC. Abstract : In conclusion, we found that checkpoint kinase 1 (CHK1) rs492510 G allele was capable of increasing the transcriptional activity of CHK1, and leading to an increased expression of CHK1, which finally contributed to a significantly higher risk of nasopharyngeal cancer (NPC) in Han Chinese population. To the best of our knowledge, the role of rs492510 in NPC has never been reported before. Our results indicated that CHK1 rs492510 might be a potential biomarker for NPC susceptibility for the first time.